(untitled) (Transport systems and technologies, 2021)
The article raises the issues of rail transport in many countries, including the European Union and Ukraine, transportation of various classes of dangerous goods, ensuring safety during their transportation, strengthening technical standards and environmental requirements for safety of dangerous goods transportation by all modes of transport and the problem of localization and liquidation of accidents during transportation of various classes of dangerous goods by rail is raised. Methods and methods of localization and elimination of spills of dangerous goods are discussed, the sorption method is described as the chosen method to solve the problem, a brief description of sorbents is given, various variants and modifications of materials for carbon sorbents are presented, materials will be used for universal sorption web, method of obtaining a universal sorption web, demonstrated a special installation for carbonization (Carbonizer), which was slightly modernized and made by the authors according to the design of the Engels University. The method of conducting experiments is described. The characteristics of the universal sorption web, its sorption properties are given, and also the technique of using the universal sorption web as a means for localization and / or liquidation of liquid hazardous substances of 3, 5, 8 hazard classes is proposed.